Profil Literasi Sains Aspek Kompetensi Peserta Didik Melalui Pembelajaran Berbasis Budaya Lokal Reyog Ponorogo - Gagan Ganiya Aulia Rahman; Insih Wilujeng; Sofyan Dwi Nugroho; Gus Rijal Mujahidin (Jurnal Penelitian Pendidikan IPA, 2023)
Students' scientific literacy can be trained by integrating local culture into learning. The integration of local culture into learning science can provide insight to students to process local culture into something meaningful in learning science. The purpose of this study was to determine differences in students' scientific literacy abilities before and after integrated science learning with local culture, the Dhadak Merak Reyog Ponorogo dance. The type of research used in this research is descriptive quantitative. The sample selection was carried out by cluster random sampling consisting of 20 students in class VII D. This research was conducted at SMP Negeri 3 Depok, Sleman, Yogyakarta. The instruments used in data collection were questionnaires, observation sheets, and scientific literacy tests on competency aspects adopted from the OECD. Data research techniques using the Wilcoxon test with the help of SPSS 25 software at Î± (0.05). The results showed that: (1) there was an increase in students' scientific literacy through learning science based on the local culture of the Dhadak Merak Reyog Ponorogo dance as indicated by the sig (2-tailed) value of 0.001 <Î± (0.05); (2) The average scientific literacy ability of students at the posttest (57.47) is higher than the average literacy ability of students during the pretest (44.12).